Selective aortic arch perfusion versus open cardiac massage in exsanguination cardiac arrest: A comparison of coronary pressure dynamics in swine. (June 2021) - Edwards, Joseph; Abdou, Hossam; Madurska, Marta J.; Patel, Neerav; Richmond, Michael J.; Poliner, David; White, Joseph M.; Rasmussen, Todd E.; Scalea, Thomas M.; Morrison, Jonathan J.
Abstract: Aim: To evaluate the mean aortic-right atrial pressure (AoP-RAP) gradients and mean coronary perfusion pressures (CPPs) observed during open cardiac massage (OCM) versus those obtained with selective aortic arch perfusion (SAAP) in post-mortem hypovolemic swine. Methods: Post-mortum, male swine, utilized in prior studies of hemorrhage, were included in the study. Animals were bled ∼25–50% of circulating volume prior to death. Animals either underwent clamshell thoracotomy and OCM immediately after death was confirmed (n = 6) or underwent SAAP within 5−15 min of death (n = 6). Aortic root and right atrial pressures were recorded continuously during each method of resuscitation using solid state blood pressure catheters. Representative five beat samples were extracted; short, similarly timed segments of SAAP were also extracted. Mean AoP-RAP gradient and CPPs were calculated and compared. Results: Mean AoP-RAP gradient and CPP were significantly higher in SAAP animals compared to OCM animals (mean ± SD; 29.1 ± 8.4 vs. 24.5 ± 5.0, p < 0.001; 28.9 ± 8.5 vs. 9.9 ± 6.0, p < 0.001). Mean CPP was not significantly different from mean AoP-RAP gradient in SAAP animals (p = 0.92); mean CPP was significantly lower than mean AoP-RAP gradient in OCM animals (p < 0.001). While 97% of SAAP segments had a CPP > 15 mmHg, only 17% of OCM segments had a CPP > 15 mmHg (p < 0.001). Conclusion: SAAP appears to create a more favorable and efficient hemodynamic profile for obtaining ROSC when compared to OCM in this preclinical porcine study.